PERAN PENYULUHAN DALAM PEMBERDAYAAN PETANI KELAPA SAWIT POLA SWADAYA DI KECAMATAN LANGGAM KABUPATEN PELALAWAN - Pratama, M. Yogi Satria; Yulida, Roza; ', Rosnita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purposes of this research are: To determine the role of extension on independent smallholder farmers of oil palm in subdistrict Langgam. To determine the empowerment level of the farmers in in subdistrict Langgam. To analize the achievement of destination extension seen from better farming, better business, and better living. To analyze effect the role of extension toward empowerment and empowerment influence to the reaching of destination extension in subdistrict Langgam. The research was conducted in Langgam subdistrict of Pelalawan. Samples were determined by purposive sampling methods with consideration that the location has active extension activities and has farmers group. 120independent smallholder farmers of oil palm were taken as respondent. Data were analyzed with descriptive analysis, Likert Scale's Summated Rating (SLR), and Structural Equation Modelling (SEM). The results showed: (1) The role of extension which consisting of a variable education, dissemination, facilitation, consultation, supervision, monitoring and evaluation as a whole are in the unfavorable category; (2) The level ofempowerment offarmers which consistingofvariablehuman resources, productiveeconomy, andinstitutionsas a whole isin the unfavorable category; (3) the purposeof role of extension which consisting of variable better farming, better bussines, and better overall living categorized good enough; (4) The relationship between the role of extension toward empowerment was shown with the value (4.247) and the relationship of empowerment toward the purpose of extension with the value (3.341). This proves that the role of extension significant effect on empowerment, as well as the purpose of extension. Â Keywords: Role of extension, empowerments, independent smallholder farmers